Fatty Acids as a Tool to Boost Cancer Immunotherapy Efficacy - Westheim, Annemarie J. F.; Stoffels, Lara M.; Dubois, Ludwig J.; van Bergenhenegouwen, Jeroen; van Helvoort, Ardy; Langen, Ramon C. J.; Shiri-Sverdlov, Ronit; Theys, Jan (Frontiers in Nutrition, 2022)
Although immunotherapy represents one of the most potent therapeutic cancer approaches, only a limited number of patients shows clinical benefit. Recent evidence suggests that patients’ nutritional status plays a major role in immunotherapy outcome. Fatty acids are essential in a balanced diet and well known to influence the immune response. Moreover, short-chain fatty acids (SCFAs) show beneficial effects in metabolic disorders as well as in cancer and polyunsaturated fatty acids (PUFAs) contribute to body weight and fat free mass preservation in cancer patients. In line with these data, several studies imply a role for SCFAs and PUFAs in boosting the outcome of immunotherapy. In this review, we specifically focus on mechanistic data showing that SCFAs modulate the immunogenicity of tumor cells and we discuss the direct effects of SCFAs and PUFAs on the immune system in the context of cancer. We provide preclinical and clinical evidence indicating that SCFAs and PUFAs may have the potential to boost immunotherapy efficacy. Finally, we describe the challenges and address opportunities for successful application of nutritional interventions focusing on SCFAs and PUFAs to increase the therapeutic potential of immunotherapeutic approaches for cancer.